The Feasibility of a Mini Dictionary of Literary Text Terms as a Learning Medium for Class XI Students at Al-Washliyah 1 Senior High School Medan - Sitompul, Devi Fitriani; Kartika, Rika; Soraya, Ratna (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This study aimed to develop a Mini Dictionary of Literary Text Terms as a learning medium for Class XI students at Al-Washliyah 1 Senior High School Medan to improve their understanding of literary concepts and terminology. Methodology: This study employed the Research and Development (R&D) method, following the Borg and Gall development model. Data collection involved observation and questionnaires. The study included 62 students from Class XI Science and Social Science streams, with a sample of 31 students from Class XI Science. Expert validation assessments were conducted by two material experts, two design experts, and a teacher. Main Findings: Validation results from Material Expert I (92%) and Material Expert II (77%) classified the dictionary as "Decent." Design Expert I (84%) rated it as "Decent," while Design Expert II (90%) categorized it as "Very Decent." The teacher’s evaluation resulted in a "Very Decent" (87%) rating. These findings indicate that the Mini Dictionary of Literary Text Terms is valid and suitable as a learning medium for Class XI students. Novelty/Originality of this study: This study introduces a specialized Mini Dictionary tailored for Class XI students, enhancing literary text learning through a structured and validated resource. The findings contribute to literacy development in Indonesian high schools by offering a pedagogically sound and validated learning tool that improves students' comprehension of literary terminology.